2019
DOI: 10.3389/fpsyg.2019.01255
|View full text |Cite
|
Sign up to set email alerts
|

Challenge and Threat: A Critical Review of the Literature and an Alternative Conceptualization

Abstract: In this article, the authors describe a new theory, the Evaluative Space Approach to Challenge and Threat (ESACT). Prompted by the Biopsychosocial model of challenge and threat (BPS: Blascovich and Tomaka, 1996 ) and the development of the Theory of Challenge and Threat States in Athletes ( Jones et al., 2009 ), recent years have witnessed a considerable increase in research examining challenge and threat in sport. This manuscript provides a critical review of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 93 publications
(133 reference statements)
1
52
0
1
Order By: Relevance
“…In the TCTSA-R, we propose a more parsimonious integration of Lazarusian ideas of cognitive appraisal and challenge and threat, and the cognitive appraisal and challenge and threat concepts put forth in the TCTSA. A recent critical review has proposed that challenge and threat states could be simultaneously activated, this co-activation can accordingly lead to individuals appraising motivated performance situations like sport as both a challenge, a threat, both, or neither (Uphill et al, 2019). Although at this time, there is no direct evidence that individuals can be challenged and threatened at the same time, in our revision, we consider that challenge and threat states are not static, and that individuals can move from one state to another.…”
Section: Cognitive Appraisalmentioning
confidence: 99%
See 1 more Smart Citation
“…In the TCTSA-R, we propose a more parsimonious integration of Lazarusian ideas of cognitive appraisal and challenge and threat, and the cognitive appraisal and challenge and threat concepts put forth in the TCTSA. A recent critical review has proposed that challenge and threat states could be simultaneously activated, this co-activation can accordingly lead to individuals appraising motivated performance situations like sport as both a challenge, a threat, both, or neither (Uphill et al, 2019). Although at this time, there is no direct evidence that individuals can be challenged and threatened at the same time, in our revision, we consider that challenge and threat states are not static, and that individuals can move from one state to another.…”
Section: Cognitive Appraisalmentioning
confidence: 99%
“…This is important because it can affect findings and influences the replicability of research findings (Sherwood et al, 1990;Shapiro et al, 1996). Assessing neuroendocrine markers of challenge and threat states, such as cortisol, and NPY, may support our understanding of psychophysiological mechanisms, as would exploring how parasympathetic nervous system activity can also relate to challenge and threat (Laborde et al, 2015;Uphill et al, 2019). Preliminary evidence suggests that high-frequency heart rate variability can be linked to challenge and threat appraisal; Laborde et al (2015) identified that, compared to baseline, greater threat responses were associated with a decrease in parasympathetic activity and Thornton et al (2019) found increased HRV after challenge instructions compared with threat instructions.…”
Section: Suggestions For Research Directionsmentioning
confidence: 99%
“…Likewise, a possible explanation for this finding may be that, during a challenge state, there is a higher quality of coping strategies that leads athletes to naturally engage in fewer verbalizations. An alternative explanation for these findings could offer support to the ESACT (Uphill et al, 2019), suggesting that individuals can be experiencing challenges, threats, neither or both. It could be argued that this finding provides support to this model as the lack of verbalized coping responses may result from athletes being both challenged and threatened, rather than alternatively challenged or threatened (as is implied by a theory that challenge and threat are on a bipolar continuum).…”
Section: Discussionmentioning
confidence: 93%
“…According to ESACT (Uphill et al, 2019) challenge and threat are not opposite ends of a bipolar continuum but rather, a unidimensional continuum and as such, individuals can be challenged, threatened, both or neither.…”
Section: Introductionmentioning
confidence: 99%
“…The biopsychosocial model of threat and challenge (Blascovich, 2008;Blascovich, & Tomaka, 1996) gives a theoretical approach for understanding the psychological responses during motivated performance, as well as an explanation of how this is indexed by physiological changes. As suggested by Uphill et al (2019), during threat the situation is appraised as self-relevant and the individual perceives insufficient personal resources to meet the demands of the task. During challenge the situation is also appraised as self-relevant, but the individual perceives enough personal resources to meet the demands of the task (c.f.…”
Section: Discussionmentioning
confidence: 99%